Índice de massa corporal e desfechos clínicos: um estudo retrospectivo durante a pandemia de covid-19 - Dal Molin, Bruna Lucas (2022)
COVID-19 is an acute respiratory disease caused by SARS-CoV-2 virus infection, which can cause severe hypoxemic respiratory failure, complications, and deaths, especially in the population with chronic health conditions. The mechanisms by which obesity may increase the severity of COVID-19 include physical mechanisms, chronic inflammation, and impaired immune function. In addition, high body mass index is a risk factor for several medical conditions that have been suggested to increase the risk of COVID-19 severity. Objective: to analyze the association between body mass index and clinical outcomes of confirmed cases of COVID-19. Methodology: Cross-sectional study, with data collection from medical records, conducted from March 2020 to December 2021. The records of medical records, biochemical and imaging tests of patients hospitalized with COVID-19 in three hospitals in the city of Francisco Beltrão (PR) were analyzed. The variables analyzed were nutritional diagnosis, age, gender, need for ICU admission, comorbidities, days of hospitalization, complications, laboratory tests and outcome. The inclusion criteria for the study were, hospitalized patients with diagnosis for COVID-19, with presence of nutritional diagnosis reported. Results: In the year 2020, 292 medical records were analyzed and in the year 2021 there were 860 medical records. Of these, only 413 had nutritional diagnosis, thus being included in this study. Were classified as normal weight 78 (18.9%), overweight 153 (37%), and obese 182 (44.1%) participants. The highest prevalence of obesity was found in females (52.5%), patients with diabetes (27.6%), patients with impaired general condition (67.9%), who presented pulmonary complications (54.5%) and arrhythmias (23%). The mean age found in obese patients was younger (55.54) compared to those classified as overweight (59.08) and normal (62.51). It was observed that the higher the BMI the lower were the values found for age (rho = -0.190), leukocytes (rho = -0.109), urea (rho = -0.145) and D-dimer (rho = -0.155). Conclusion: This study provides evidence that overweight and/or obesity then associated with a worse clinical picture during hospitalization of patients with COVID-19. Regarding the frequency of death, there was no statistical difference in relation to nutritional diagnosis.